Dynamic Imaging of Carbon Nanotube - Liquid Crystal Suspensions. - Bjorkman, Raymond N. (Tufts Archival Research Center, 2015)
Liquid crystals (LCs) are materials that exhibit fluid-like properties, while maintaining a degree of long-range crystalline order. They exhibit a variety of useful electro-optical properties and have found wide use in liquid crystal displays, optical telecommunications, and soft actuators. The speed at which the material responds to an applied electric field (switching speed) is a critical determinant of device performance. To study the spatiotemporal dynamics of LC materials, a novel method combining high-speed imaging with polarized light microscopy was developed, which provides micron spatial resolution and millisecond temporal resolution. This method was validated by quantifying the switching dynamics of a well-characterized liquid crystal (5CB) in a canonical Fréedericksz cell geometry. High-speed polarization microscopy was then applied to measure the effect of carbon nanotube (CNT) dopants on LC switching dynamics. CNTs are found to reduce the switching speed by about 10% compared to pure 5CB liquid crystal over voltages ranging from 2.5 – 3.5V.